The impact of entrepreneurial activities and college students’ entrepreneurial abilities in higher education—A meta-analytic path - Hua, Jieyu; Zheng, Kongdi; Fan, Supei (Frontiers in Psychology, 2022)
The purpose of this study is to quantitatively analyse 34 independent papers collated from both domestic and international literature on the correlation between university entrepreneurial activities and college students' entrepreneurial abilities by means of meta-regression analysis and to examine in detail the significant factors affecting the entrepreneurial competencies of university students. The study revealed a significant positive relationship between entrepreneurial activities in universities and university students’ entrepreneurial ability, and further explored the extent to which each of the three types of entrepreneurial activities had an impact on college students' entrepreneurial abilities. Then, the effects of different moderating variables on the relationship are further analysed. The results show that the type of university, economic development, gender ratio, age structure, and time to publication all significantly moderate the degree of correlation between university entrepreneurial activities and college students' entrepreneurial abilities.